PERFORMANCE LOSSES CAUSED BY Phenacoccus herreni Cox & Williams IN TWO YUCCA CLONES - VARGAS-H., OCTAVIO; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 1984)
This research was conducted at Centro Internacional de Agricultura Tropical (CIAT) located at 1006 meters above sea level) with an average annual precipitation of 806.2 mm. Cassava mealybugs constitute one of the world’s major pests, causing severe damage to the crop in America and Africa. There are two major species, Phenacoccus terrain, and P. manihoti Matile-Ferrero. Both species are present in Ameri ca. In Africa, only P. manihoti is causing significant field losses. The objective of this experíment was to determine the yield losses that P. herreni can cause to cassava plants under CIAT-Palm ira conditions. In this study, two varieties were used: M Col 22 and CMC 40 in a split-plot experimental design. Three-month-old cassava plants were artificially infested with one ovisac and two adult females per plant age. The following data were taken monthly: plant height, population grade, and damage grade. At harvest time yield, the number of commercial roots, the number of selected stakes, and starch content were determined. The results indicate that the varieties M Col 22 and CMC 40 had yield losses of 88.3% and 67.9% respectively; plant height can be reduced up to 33%, which affect the number and quality of the selected stakes; depending on the variety, the stake losses can reach 74%. Population grade and damage showed highly significant differences within treatments; there was a 23.5% differerce in population grade between M Col 22 and CMC-40 (with mealybugs); likewise, the reduction in starch content was higher for M Col 22 (16.1%) than in CMC 40 had only 4.9%. These results show that the mealybug P. herreni can cause severe yield losses in cassava crops in areas with favorable environmental conditions for the post.